Epistolary novel and women writers: Fatma Aliye, Halide Edip Adıvar and Şükûfe Nihal Başar - Dereli, Bihter. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
This thesis examines the epistolary novels by women writers in Turkish literature from Tanzimat to early Republican period. These epistolary novels fundamentally depend on the "female I" narrator. This thesis focuses on the female voice that women writers bring out in the epistolary novels, Fatma Aliye’s Levayih-i Hayat, Halide Edip Adıvar’s Handan and Şükûfe Nihal Başar’s Çöl Güneşi. In these novels, female voice is represented by "female I" narrator who discusses and questions the contemporary ideas regarding issues like marriage, woman’s education and gender. Arguing that women writers preferred the epistolary novel in order to raise a female voice and through its techniques they offer a representation of female individuality, I try to prove that these three novels bring out female voice beyond their time. However, I also underline that female sexuality is restricted in these novels through the moral codes of society.
Keywords: Epistolary fiction.; Women authors, Turkish.